Quality Improvement of Chicken Meat Treated with Neutral Electrolyzed Water - Ali Meawad Ahmed; Mona Mohammed Eissawy; Ibrahim Mohamed Fares; Taghreed Ahmed Hafez; Nada Ibrahim Hussein (Universitas Airlangga, 2025)
Background: Chicken meat during processing may be exposed to bacterial contamination through several different ways. Electrolyzed water, as a new sanitizer, has gained popularity in food industry among many countries in recent years. The usage of electrolyzed water is a prospective, green conception and has several characteristics over conventional cleaning procedures which are safe for human beings and the environment. Purpose: This study was aimed to determine the sensory and bacteriological quality of chicken carcasses treated with different types of electrolyzed water. Method: Thirty-seven freshly slaughtered broiler chicken carcasses were completely immersed in clean container containing distilled water and electrolyzed water for 40 minutes, then sensory evaluated. For bacteriological analysis, chicken carcasses were divided into three groups, one for control, another group (Group I and II) and the chicken meat samples treated by immersion in neutral electrolyzed water for 20 and 40 minutes, respectively. Results: The mean value of colour scores of treated chicken carcasses was 4.9, 2.8, 4.5 and 3.7, for odour scores of treated chicken carcasses was 4.8, 2.6, 4.6 and 3.4, for general appearance scores of treated chicken carcasses was 4.9, 3.6, 4.6 and 3.9 for control, acidic, neutral and alkaline electrolyzed water, respectively. The bacteriological quality of treated chicken meat with neutral electrolyzed water was assessed. The mean values of aerobic plate counts for control, after treatment for 20 and 40 minutes were 5.40, 3.90 and 3.71 Log10 cfu/g, for enterobacteriacea were 3.63, 2.69 and 2.59 Log10 cfu/g, for Staphylococcus aureus were 2.99, 2.57 and 2.22 Log10 cfu/g, for Escherichia coli were 2.93, 2.18 and 1.94 Log10 cfu/g, respectively. Conclusion: The results indicated immersion of chicken carcasses for 20 minutes in neutral electrolyzed water improved their bacteriological quality without adverse effect on sensory quality.